TRACING THE MEANING OF RASTRA SEWAKOTTAMA'S PHILOSOPHY AS A TOOL FOR CONTROLLING VIOLATIONS IN POLICE MANAGEMENT (STUDY AT PALOPO CITY POLICE STATION) - Bahri, Syamsul; Salju; Rismawati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
This study aims to reveal the meaning of Rasta Sewakottama in human resource management at Palopo City Police Station. Using qualitative phenomenological methods, this research found that to improve organizational performance, reduce violations of laws and violations of the code of ethics required collective awareness, a sense of responsibility, respect for differences and self-development. This can be achieved optimally by the example of the leader and the ability of the Human Resources unit to place personnel. Formation is done through weekly activities such as spiritual guidance and counseling. In addition, optimization of information systems is used by the National Police to monitor the performance of each personnel. The meaning of the philosophy of Rasta Sewakottama according to the Palopo City Police Chief is the deepest awareness of all police members to carry out state duties as guardians of public order and security. Through this personal awareness, the potential for violating the code of ethics and other violations of the law can be minimized.